PHYSICAL AND MECHANICAL CHARACTERISTICS OF THE EARTHEN BARNS USED FOR FOOD CROP STORAGE IN THE NORTH>WEST OF BENIN (WEST AFRICA) - GIBIGAYE, ADAM MOHAMED; ZEVOUNOU, CRÉPIN; GBAGUIDI AÏSSE, GÉRARD LÉOPOLD; KAKI, CHRISTOPHE (My University, 2013)
Atacora and Donga are two departments regarded as the barns of Benin. In these two regions, the surplus of food crops harvested by farmers is stocked in earthen barns whose primary construction material is kneaded clay soil with an admixture of vegetable straws (fonio, rice…) pounded beforehand. The following research is designed to scrutinize the variation of compression strength and/or tensile strength of the used earthen material with respect to the optimum straw content, and the fluctuation of the fracture related parameters. Laboratory tests have shown that an optimum straw content of 2% provides the highest compression strength with the best mechanical performances in terms of cohesion and internal angle of friction. Tensile strength, however, continues to increase with higher straw percentages with no breakpoint indication. Moreover, the laboratory determination of the composite material’s modulus of elasticity has proven that the used soil does not have a linear elastic behavior.
Keywords: Earthen barns; clay soil; vegetable straws; strength; fracture related parameters